Expression Profiling and In Vitro Analysis of Olfactory Epithelial Stem and Progenitor Cells. - Krolewski, Richard. (2017)
Abstract: The olfactory sensory neurons (OSNs) of the olfactory epithelium (OE) are under constant stress from environmental insults, yet despite damage to and death of these OSNs, the OE maintains ability to detect and transmit odorant stimuli. Globose basal cells and horizontal basal cells (GBCs and HBCs)- OE stem and progenitors- are responsible for this functional maintenance, which involves regeneration of OSNs and other cell types as needed. We have taken three approaches to understand how GBCs and HBCs accomplish this: (1) global expression profiling, (2) in vitro analysis and transplantation of olfactory neurospheres, and (3) characterization of Ascl1 mutant mice displaying widespread neurogenic failure. Expression profiling of upstream Sox2(+) GBCs, Neurog1(+) GBCs, and OSNs has revealed a common expression signature, as well as a separate cohort of genes enriched in the classes of GBCs isolated. The expression of LSD1 and coREST, two proteins enriched in GBCs and associated with chromatin modification, suggests a role for these proteins in progenitors of normal and lesion-recovering OE. Expression profiles also reveal a cohort of odorant receptors showing maximal expression in progenitors, suggesting that a number of these odorant receptors may be previously unidentified non-functional receptors. In vitro analysis of neonatal olfactory neurospheres (ONS) indicates that maintaining 3-D architecture is crucial for the ability of ONS-derived cells to engraft into lesion-recovering host epithelium. ONS also permits modeling of epithelial-stromal interactions. Conditioned media from activated, stroma-derived cells influence the cellular composition of ONS. These influences are also reflected in post-transplantation outcome of ONS-derived cells cultured in stromal-derived factors. Examination of the developing OE on a background of neurogenic failure in Ascl1 knockout mice reveals striking interrelationships between progenitor cells. The phenotypes and emergence of GBCs and HBCs are dramatically altered. Appearance of HBCs is delayed, while Notch1-expressing GBCs and cKit-expressing GBCs are undetectable in regions of neuron depleted OE. The findings described in this dissertation highlight the coordinately regulated genes in progenitors and neurons, describe factors that influence the in vitro composition and engraftment capacity of neurogenic progenitors, and reinforce the interactions of these progenitors and the altered cellular phenotypes resulting from failure of neurogenesis.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisor: James Schwob.; Committee: Karina Meiri, Charlotte Kuperwasser, John Castellot, and Lee Rubin.; Keywords: Cellular biology, Neurosciences, and Bioinformatics.